Cdc25 Inhibited In Vivo and In Vitro by Checkpoint Kinases Cds1 and Chk1 - Furnari, Beth (The American Society for Cell Biology, 1999)
In the fission yeast Schizosaccharomyces pombe, the protein kinase Cds1 is activated by the S–M replication checkpoint that prevents mitosis when DNA is incompletely replicated. Cds1 is proposed to regulate Wee1 and Mik1, two tyrosine kinases that inhibit the mitotic kinase Cdc2. Here, we present evidence from in vivo and in vitro studies, which indicates that Cds1 also inhibits Cdc25, the phosphatase that activates Cdc2. In an in vivo assay that measures the rate at which Cdc25 catalyzes mitosis, Cds1 contributed to a mitotic delay imposed by the S–M replication checkpoint. Cds1 also inhibited Cdc25-dependent activation of Cdc2 in vitro. Chk1, a protein kinase that is required for the G(2)–M damage checkpoint that prevents mitosis while DNA is being repaired, also inhibited Cdc25 in the in vitro assay. In vitro, Cds1 and Chk1 phosphorylated Cdc25 predominantly on serine-99. The Cdc25 alanine-99 mutation partially impaired the S–M replication and G(2)–M damage checkpoints in vivo. Thus, Cds1 and Chk1 seem to act in different checkpoint responses to regulate Cdc25 by similar mechanisms.